Selectivity and Internal Migration: A Study of Refugees' Dispersal Policy in Sweden - Haberfeld, Yitchak; Birgier, Debora Pricila; Lundh, Christer; Elldér, Erik (Frontiers in Sociology, 2019)
Following the intensified waves of refugees entering Europe, dispersal policies for newly arrived refugees have been proposed to speed up their integration in the hosting societies and to share the financial burden associated with their integration across and within the EU countries. The effectiveness of dispersal policies depends, among other factors, on the extent to which refugees tend to stay in the initial location they are assigned to live in, and on their patterns of self-selectivity during subsequent moves of internal migration. Economic theories of migration suggest that highly skilled and motivated economic immigrants tend to migrate to labor markets with broader opportunity structures, while less capable individuals choose markets that are more sheltered. We use a quasi-experimental design to examine the extent to which economic theories of migration apply not only to economic immigrants, but to refugees as well. We focus on a refugee cohort that came to Sweden during a period when the so-called "Whole-Sweden" policy was in effect. This policy was designed to reduce the concentration of refugees in the larger cities by randomly deploying asylum seekers in almost all municipalities across Sweden. After being assigned to an initial location, refugees were given the choice whether to remain in their initially assigned location or move to another place in Sweden. Such a policy allows us to examine refugees’ self-selection patterns within Sweden and their effect on their subsequent earnings assimilation. We use individual register data from Statistics Sweden to study all refugees who arrived in Sweden during 1990-1993, and we follow each one of them during an 8-year period from the time they were granted residency. We use discrete-time survival analysis (complementary log-log models) in order to assess the effects of abilities on the destination choices of refugees, and individual fixed-effect models to assess the effects of internal migration on their income. Destinations were defined on the basis of the economic opportunities they offer. The results suggest that refugees’ relocation choices have positive effects on both refugees' income growth and their social utility.